Hemocyte Types Based on Total and Differential Counts in Samia cynthia ricini (Lepidoptera; Saturniidae) Reared on Host Plants Versus an Artificial Diet - Tungjitwitayakul, Jatuporn; Tatun, Nujira (Naresuan University Journal: Science and Technology (NUJST), 2019)
Hemocytes are an important component of the insect immune system because of their involvement in coagulation, phagocytosis, and encapsulation. The larvae of the eri silkworm, Samia cynthia ricini , has been successfully used as insect model to study the innate immune response and antibacterial activity. This insect grows on host plants, such as cassava and castor leaves, and on artificial diets. Several studies have revealed that artificial diets alter the insect’s immune responses. Hence, it is important to assess the concentration of hemocytes in S . cynthia ricini reared on the host plant (castor leaves) and an artificial diet. The hemocytes of S . cynthia ricini are classified into five types: prohemocytes (PRs), plasmatocytes (PLs), granulocytes (GRs), spherulocytes (SPs), and oenocytoids (OEs). The total hemocyte count (THC) was studied in four developmental stages, including 3 rd -, 4 th -, and 5 th -instar larvae, in addition to pupae. The results indicated that the THC in larvae reared on castor leaves decreased gradually in later developmental stages. In contrast, the THC in larvae reared on an artificial diet were at lower levels in all stages. The differential hemocyte count (DHC) indicated that ratio of each hemocyte type was comparable during larval and pupal stages in which PLs were most abundant, followed by GRs, SPs, PRs, and OEs in both groups. Furthermore, the diet had different effects on the percentage of PLs, GRs, and PRs during larval and pupal stages. Since the immune system of eri silkworm was interfered, this artificial diet may not suitable for rearing system in immunological study aspect. Keywords: eri-silkworm, hemocytes, castor leave, artificial diet, immunity